Angiopep‐Conjugated Electro‐Responsive Hydrogel Nanoparticles: Therapeutic Potential for Epilepsy1. (18th July 2014) - Ying, Xiaoying; Wang, Yi; Liang, Jiao; Yue, Jiaxing; Xu, Cenglin; Lu, Lina; Xu, Zhenghao; Gao, Jianqing; Du, Yongzhong; Chen, Zhong
Abstract A safe and effective therapy for epilepsy requires a drug delivery system that can penetrate the blood–brain barrier and subsequently release antiepileptic drugs rapidly to suppress neuronal discharges in a timely manner. We have developed electro‐responsive hydrogel nanoparticles (ERHNPs) modified with angiopep‐2 (ANG) to facilitate the delivery of the antiepileptic drug phenytoin sodium. The resulting ANG‐ERHNPs had an average diameter of (102.3±16.8) nm and were electro‐sensitive with regard to particle size and drug release in vitro. ANG‐ERHNPs have the characteristics of penetrate the BBB easily, resulting in a higher distribution in the central system. The improved antiepileptic effects were investigated with the amygdala kindling model. The results demonstrate that the ANG‐ERHNPs were able to transport antiepileptic drugs into the brain and release them under electroencephalograph epileptiform abnormalities to greatly improve the therapeutic index of existing drugs in clinical use.